Estimating a regional ventilation-perfusion index. (June 2015) - Muller, P A; Li, T; Isaacson, D; Newell, J C; Saulnier, G J; Kao, Tzu-Jen; Ashe, Jeffrey
Abstract This is a methods paper, where an approximation to the local ventilation-perfusion ratio is derived. This approximation, called the ventilation-perfusion index since it is not exactly the physiological ventilation-perfusion ratio, is calculated using conductivity reconstructions obtained using electrical impedance tomography. Since computation of the ventilation-perfusion index only requires knowledge of the internal conductivity, any conductivity reconstruction method may be used. The method is explained and results are presented using conductivities obtained from two EIT systems, one using an iterative method and the other a linearization method.